Paris [compact disc, unabridged] - Rutherfurd, Edward (Random House Audio : Books on Tape, 2013)
From the grand master of the historical novel comes a dazzling epic portrait of Paris that leaps through centuries as it weaves the tales of families whose fates are forever entwined with the City of Lights. The breathtaking multigenerational saga takes listeners on a journey through thousands of years of glorious Parisian history, through intimate and vivid tales of characters both fictional and true, and with the sights, scents, and tastes of Paris come to sumptuous life.